(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The contemporary landscape of Assam is at a critical juncture, grappling with the intricate interplay between economic development, sustainability, and mounting environmental concerns. As Assam experiences an uptick in economic activities, the diminishing availability of natural resources poses a significant threat to its delicate ecosystem. Such degradation amplifies environmental adversities such as droughts, acid rain, and erratic rainfall patterns, leading to devastating consequences for its residents. Furthermore, riverbank and soil erosion have rendered many inhabitants homeless, particularly those along riversides and landslide-vulnerable terrains. Tragically, displacements spurred by these hazards often lead to encroachments into forested zones, intensifying concerns about deforestation. Another emerging issue is the encroachment of desertification, mainly driven by unchecked and ill-planned urbanisation. These factors not only escalate the threats of global warming but also jeopardise the livelihoods of Assam’s population, pushing many into poverty. Displaced individuals face the loss of traditional livelihoods and confront challenges related to security and identity. This research aims to shed light on the multi-faceted challenges birthed by environmental degradation in Assam, focusing on its impacts on livelihood and housing. It also endeavours to propose actionable measures to alleviate the hardships caused by environmental depletion.